Identifikasi Citra Paru-Paru pada Pasien COVID-19 dengan Teknik Edge Detection - Marisha Pertiwi (Jurnal Sistim Informasi dan Teknologi, 2022)
X-ray chest radiographs produce digital radiographic images of the chest area such as the lungs, heart and ribs. This image can visualize the lung condition of patients with COVID-19. The Edge Detection technique can see the edges of objects in the lungs of COVID-19 patients more clearly. The lungs of patients with COVID-19 are damaged due to the GGO (Ground Glass Opacity) COVID-19, namely there is white fog, the lungs look blurry at the edges or areas affected by the disease and also affect the area of ​​​​the area. This technique can make it easier for health workers to see X-ray results on objects in the lungs of COVID-19 patients and assist doctors in handling COVID-19 patients. With advances in the computer field in the application of image processing techniques, this Edge Detection Technique uses Matlab software to obtain edge and area images of clean lungs in COVDI-19 patients. The data used in this study were 30 samples of lung images of COVID patients and 10 images of healthy patients' lungs as a comparison sourced from Embung Fatimah Hospital Batam, which were processed in the grayscale stage, then the image was preprocessed with Intensity Adjustment then segmented with Active Contour and then using Edge Detection Technique. The results of this study were as many as 22 lung images produced an accuracy value of 73%. The image of the test results with the Edge Detection Technique to identify the edges of the object's lungs of COVID-19 patients which are quite clear by producing white pixels that are so visible. The perimeter of the right lung of COVID-19 patients ranged from 110,897 - 261,254 mm and Area 267,719 - 940,668 mm2, Perimeter of the left lung ranged from 114,613 - 262,943 and Area 170.616 - 856,993 mm2, while healthy patients as comparison had the right lung Perimeter range of 187,598 -270,624 and Area 514,947 - 1025.44 mm2, Perimeter of the left lung 182,226 - 287,358 and Area 480,592 - 901,418 mm2 means that COVID-19 virus infection reduces lung area, the range of COVID-19 lungs is lower than healthy lungs.